COMBINED HEATING SYSTEM FOR SOLAR GREENHOUSES BASED ON HEAT PIPES AND BIOMASS ENERGY - Fatilloev , Sukhrob; Rakhmatov, Obid (Innovatsion texnologiyalar, 2023)
The article discusses the possibility of using heat pipes to utilize the thermal energy of biomass and greenhouse soil in order to maintain optimal temperature conditions. A calculation scheme for the heat balance of a solar greenhouse with a combined heating system based on heat pipes and biomass energy has been developed. A mathematical module of the thermal balance of a solar greenhouse has been compiled. With heat pipes, the main thermal parameters of the proposed system are justified. It has been established that the use of heat pipes in heating systems ensures the recovery of heat from the heated layer of biomass and covers 20-30% of the thermal load of a greenhouse with a useful area of 100 m2.